Answer:
i think this is it
Step-by-step explanation:
the answer i got is just 55
9514 1404 393
Answer:
A(x) = 20000(0.88)^x
Step-by-step explanation:
The general form of these exponential equations is ...
A(x) = a·b^x
where 'a' is the initial value, and b is the annual growth factor. x is the elapsed time in years.
The growth factor is ...
growth factor = 1 + growth rate
Here, the growth rate per year is -12%, so the growth factor is ...
b = 1 -12% = 88% = 0.88
Of course, the initial value is a=20,000, so the equation is ...
A(x) = 20000(0.88)^x
Answer:
x=-6
Step-by-step explanation:
Let x be the number
3x = x^2 -54
Subtract 3x
3x-3x = x^2 -3x-54
0 = x^2 -3x-54
Factor
What 2 numbers multiply to -54 and add to -3
-9*6 = -54
-9+6 = -3
0=(x-9) (x+6)
Using the zero product property
x-9=0 x+6=0
x=9 x=-6
The questions asks for the negative solution
x=-6